25th International Bremen Film Conference: digital event from May 5 - 8, 2021 - Brachert, Wanda (Research and Humanities in Medical Education, 2021)
This year’s Conference title is Mind/Screen and it is all about mental illness and film. Screenings include the German premiere of Psychosis in Stockholm (2020) by director Maria Bäck and Jessica Hausner’s thriller Little Joe (2019). Films and thematically appropriate lectures and discussions are mostly in english and can be viewed online. Please check the PDF of the Festival Booklet for details of the keynotes, the symposium, and the films.